Evaluation of glycemic index, glycemic load and biochemical traits of rice associated with anti-diabetic properties - Rithesh, B N; Ramchander, S; Manonmani, S; Uma, D; Rajeswari, S; Jeyaprakash, P (Plant Science Today, 2025)
Diabetes mellitus, a modern lifestyle disease and metabolic disorder, is closely associated with an increased risk of cardiovascular disease. Research on carbohydrates, particularly white rice with a high glycemic index, has been linked to an increased risk of type II diabetes, heart disease, and cancer. In this study, we aimed to understand the nutritional composition, estimated glycemic index, and glycemic load of twenty-eight rice accessions, particularly focusing on those with low starch digestibility associated with low GI levels. The proximate composition analysis revealed that tested rice accessions exhibited higher levels of genetic variation for amylose (18.45 - 25.97%), phenolic content (5.00-34.08%), protein (5.52-14.54%), and crude fibre (1.64-3.91%) content in brown rice. Huge variability for estimat?ed glycemic index, ranging from low to high GI was observed among all the varieties (49.37 - 78.58%). Traditional varieties viz., Thavalakannan and Kavuni depicted low estimated glycemic index (49.37 % and 54.55 %) and moderate glycemic load (14.60 and 15.80), respectively. The estimated glycemic index exhibited significant and negative association with amylose (r = -0.57**), phenolic (r = -0.67**), and crude fibre (r = -0.52**) content. In contrast, glycemic load showed a significant positive correlation with the amount of carbohydrate content. Principal component analysis revealed considerable variability among rice accessions' biochemical traits with the first two principal components accounting for 68.57% of the total variance. The hierarchical clustering based on Darwin software identified two major clusters. Cluster I comprise popular varieties and Cluster II contains traditional varieties with low to moderate glycemic index. Moreover, identifying rice varieties with lower glycemic index can facilitate the development and enhancement of breeding lines for the diabetic population.